THE PAYMENT OF INCENTIVE TO INCREASE THE PERFORMACES OF THE EMPLOYEES OF FOOD AND BEVERAGE SERVICE DEPARTMENT AT STARS HOTEL IN SAMOSIR REGENCY - Syahrul (Akademi Pariwisata Darma Agung, 2022)
This research aims to know the impacts of incentive payments to the staffs of Food and Beverage Service Department at star hotels in Regency Of Samosir. This is a clausal resaerch to analyze how a variable impacts another variable whre the independent variable got controlled treatment to see theimpacts to dependent variable.This research takes selected 100 samples Data collected by physical observation, literary study, interview, and personnel questionnaires. Data analyzed descriptively using impact analysis method. The research shows that the financial incenti payment to the staffs of Food and Beverage Service Department for star hotels in Samosir Regency gets impacts toward the increasing of employees work performances for 68,80 %. The payments of financial incentive has significant and positif correlation toward the increasing of employees work performances of Food and Beverage Service Department for star hotels in Samosir Regency. There is strong correlation between financial incentive payment toward the increasing of employees work performances in Food and Beverage Service Department of star hotels in Samosir Regency.